High-grade metamorphic rocks from Skallevikshalsen in the Lutzow-Holm Complex, East Antarctica: metamorphic conditions and possibility of partial melting - Yoshimura, Yasutaka; Motoyoshi, Yoichi; Miyamoto, Tomoharu; Grew, Edward S.; Carson, Christopher J.; Dunkley, Daniel J. (National Institute of Polar Research, 2004)
P(論文) The high-grade metamorphic rocks of Skallevikshalsen, Lutzow-Holm Complex, East Antarctica predominantly comprise garnet-sillimanite gneiss, garnet-spinel-sillimanite gneiss, garnet-biotite gneiss and garnet-two pyroxene-mafic granulite. The metamorphic conditions were estimated using various geothermometers and geobarometers for garnet-biotite gneiss and mafic gneiss. The results were 770-940℃and 0.65-1.2 GPa for garnet-biotite gneiss and 780-960℃ and 0.6-1.1 GPa for mafic gneiss. Garnet-biotite gneiss is widespread in this area and displays a well-developed migmatitic structure. Garnet porphyroblasts in the leucosome and the boundaries between leucosome and melanosome in garnet-biotite gneiss commonly have a poikiloblastic texture with euhedral feldspar and quartz inclusions. High Y concentrations in garnet cores, high An values for plagioclase inclusions, and high Ba contents in K-feldspar from garnet-biotite gneiss are inferred to reflect growth in the presence of partial melt. Garnet in garnet-sillimanite gneiss also has high Y and P contents and chemical zoning that implies changes in trace element distribution coefficients. It is suggested that hydrous melt in garnet-sillimanite gneiss was generated during prograde metamorphism while anhydrous restite underwent continuous high-temperature metamorphism. Garnet-sillimanite gneiss is likely to be the restitic product of partial melting and shows evidence for melt segregation and movement. departmental bulletin paper